It’s F=10
6(3) - 2(4) = 18 - 8= 10
Answer:
−5xy^2+y^3+25x^2−5xy−y^2
Step-by-step explanation:
25x^2−5xy−5xy^2+y^3−y^2=
25x^2−5xy−2
———————————-
<em>Please refer to the attachment for the answer and explanation. Hope it helps!!</em>
For all just put them together in x and y. For example, f(2)=-2 would be (2,-2). f(1)= 1 would be (1,1).
Answer:
312
Step-by-step explanation:
is equivalent to 0.25
<h2>{6x[2+(16-5)]}/0.25=</h2><h2>{6x[2+11]}/0.25=</h2><h2>{6x13}/0.25=</h2><h2>78/0.25=</h2><h2>312</h2>
<em>It's big so you can see better.</em>